RETRACTED: RCE-Kmeans Method for Data Clustering - Izmy Alwiah Musdar; Azhari Azhari (Universitas Ahmad Dahlan, 2015)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in International Journal of Advances in Intelligent Informatics to article entitled “RCE-Kmeans Method for Data Clustering” Vol 1, No 2, pp. 107-114, July 2015, DOI: http://dx.doi.org/10.26555/ijain.v1i2.38.This paper has been found to be in violation of the International Journal of Advances in Intelligent Informatics Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Indonesian Journal of Computing and Cybernetics Systems, Vol. 9, No. 2 (July 2015), pp. 157-166, DOI: http://doi.org/10.22146/ijccs.7544, entitled